Effects of nano silver as bactericide on beneficial bacteria, uptake by plant and impact on plant growth - Satoodehnia, Poopak (2019)
Nanotechnology refers to the use of nano –size particles (measuring < 100 nm) in various fields including agriculture. Nanoparticles can be in the form of nano pesticide, nano fertilizer, waxing and sensors that are currently being used in agriculture. However, there is little information on the effects of these particles on microorganisms in soil and its impact on the environment. Therefore, this study was undertaken to evaluate the effect of nano-silver as bactericides on selected plant growth-promoting bacteria, residue in soil and its uptake in plant and impact on plant growth. In the initial study, the minimum inhibitory concentration (MIC) of nano-silver on beneficial microbes from the soil and pathogen was determined. To evaluate the MIC of silver nanoparticles (AgNPs), the size and shape of nanoparticles were determined by transmission electron microscopy (TEM) and scanning electron microscopy (SEM). To evaluate the effect of nano-silver on beneficial microbes, a total of 13 beneficial microbes tested for this study by using microdilution broth method. In the second study the effect of nano-silver against Ralstonia solanacearum and its effect on seed germination was studied. Based on the MIC results 40 ppm of nano- silver was used while different treatments were set for this study. On the third study the leaching potential of nano- silver in different soils samples were investigated. For leaching study, 196 μl of nano- silver was added to the two soils samples and leachate were collected every day for 14 days. Three replications including control were arranged as a completely randomized design (CRD) experiment and later the silver were measured by inductively coupled plasma optical emission spectrometry (ICP–OES). The forth study was aimed to analyze the residue of nano- silver in plant and also effect of nanosilver on plant growth. In this study Cucumis sativus’s seed were soaked with different concentration of nano- silver (16, 24, 32 and 40 ppm) and control was not treated with nano-silver. This study was conducted in a glasshouse and the treatments were chosen based on the MIC results and the Munchong series soil, sand and organic matter were used as mixture for this study. Samples were analyzed with ICP-OES to detect the residue of silver using destructive sampling. Three different time (3WAP, 6WAP and 8WAP) were used for sampling time. Results showed that nanoparticles were pure spherical entities with 16 ± 6 nm in size. Nano- silver inhibited the activity of bacteria and pathogen on the range of 12 – 40 ppm. Results showed that silver nano particles increased the seed germination and protect the seed from pathogen. The physico- chemical data indicated that Munchong series soil sample was acidic (pH~ 5) and the amount of clay was approximately 70 %. However, the reference soil sample (with ratio of 2:2:1 Munchong series soil, sand and organic matter) was slightly acidic (pH ~ 6.6) and the amount of sand was 60 %. Results showed that the cation exchange capacity (CEC), electrical conductivity (EC), micro and macro elements were higher in the reference soil sample which could be due to the organic matter (cow dung) that was used. Results also showed that no silver was detected in leachate of all treatments that might be due to the amount of clay, organic matter in samples. However, another possibility could be due to less amount of silver that was applied to the soil. For the uptake study, results showed that residue of silver was detected in root, stem, flower and fruit during different sampling times. Results also indicated that by increasing the concentration of nano-silver the dry weight of plant was also increased. However, nano- silver did not affect the length of stem, root length. Silver nanoparticles is shown to affect root diameter (RD) and root volume (RV) and leaf area index (LAI) which depends on the time of exposure. Thus at the third sampling, silver increased the LAI, RD and RV.